Pengungkapan Green Intellectual Capital: Studi Deskriptif - Dyna Rachmawati; Yosephien Paskalis (Jurnal Akuntansi, 2022)
This study aims to describe the disclosure of green intellectual capital (GIC). GIC has not been widely explored in previous studies, especially in Indonesia. Therefore, this research will conduct a descriptive study of all public companies listed on the Indonesia Stock Exchange (IDX) with an observation period of 2020. The data collection method is documentation based on management letters in annual reports. The management letter used in this study consists of two reports, namely the report of the board of commissioners and the report of the board of directors. Management letters can be regarded as a new source of data used by companies to disclose GIC information. GIC disclosure is measured using the content analysis method on keywords that represent each GIC component. The results of the descriptive study show that, first, the financial (agriculture) is the sector that most (little) expresses GIC. Second, structural capital (environmental capital) is the most (little) GIC component disclosed in management letter. The results of this study contribute, first, practically; management in companies with GIC disclosure levels has special attention to the importance of sustainability through green innovation. Second, structural capital is the easiest component to disclose in a management letter because management’s main concern is capital expenditure. Third, academically; the results of this study can enrich the GIC literature in Indonesia Keywords: environmental capital, green intellectual capital, human capital, relational capital, structural capital